Are European Elections Still Second-Order? A Study of Spain and Portugal - Fernando Martínez Arribas; Celso Cancela Outeda; Bruno González Cacheda (População e Sociedade)
This paper addresses the issue of ‘second order’ elections as applied to the electoral results of the 2019 and 2024 European Parliament elections in the Iberian states. Specifically, it aims to analyse whether these elections can be classified within this category. To achieve this objective and answer the research question, we have analysed through descriptive statistics the information related to three study variables extracted from the conceptual model adopted: level of electoral participation; strategic or affective orientation and motivation of the vote; level of support for the ruling party. The results show contrasting trends in relation to the expected values. In conclusion, we must point out the impossibility of effectively framing the elections analysed in the second-order category. We can affirm that the analytical model traditionally used presents important limitations in contexts of change and recomposition in party systems.